Collecting the 20th century - Franklin, Adrian (UNSW Press, 2010)
In this lavishly illustrated book, Adrian Franklin, TV presenter, writer and serious collector, takes a decade-by-decade approach to exploring the twentieth century - the architecture, fashion, design and everyday material culture. Covering popular periods such as Arts and Crafts, Art Nouveau, Industrial Arts, Art Deco, Mid-Century, Retro, Modern, this book combines useful information with personal reflection in a lively and entertaining style.